Citrinal líquido® en el agua de bebida y su efecto sobre parámetros productivos y de salud en pollos COBB 500 - López Loor, José Daniel (2024)
The objective of this study was to evaluate the effect of Citrinal Liquid® at doses of 1 ml and 1.5 ml per liter of water compared to a control on productive and health parameters in Cobb 500 chickens. A total of 180 chickens were used under a Completely Randomized Design (CRD) divided into 18 experimental units, distributed across 3 treatments: T0 (no Citrinal addition), T1 (1 ml Citrinal) and T2 (1.5 ml Citrinal) in the drinking water, with 6 repetitions, each comprising 10 observational units. The evaluated variables included weight gain (kg), cumulative feed intake (kg), feed conversion ratio (kg/kg), European efficiency index (value), carcass yield (%), viability (%), mortality (%), weight of lymphoid organs (thymus, spleen, Fabricius bursa) (g), and cost-benefit ratio. In the productive parameters, no significant differences were found for final weight (p-value 0.1395), or feed conversion ratio (p-value 0.2353). However, significant differences were reported for cumulative feed intake (p-value 0.0346) and the European efficiency index (p-value 0.0052), notably showing differences were observed between T1 and T0. For health indicators (p-value 0.3911), no differences were observed in the weight of lymphoid organs. It is concluded that the use of Citrinal Liquid® in drinking water does not yield significant differences but there are numerical differences, with the treatment of 1 ml/L of Citrinal Liquid® achieving better results in each of the productive and health parameters.